2022
DOI: 10.1111/hir.12426
|View full text |Cite
|
Sign up to set email alerts
|

Graduate students in public health predict their actual usage of different library services and resources quite accurately

Abstract: Background: Public health students need to use different resources to those used by other health science students.Objectives: To compare how users expect to interact with library resources and services with how they reported actual interactions and expected future usage, to inform library planning.Methods: During first semester orientation, a paper questionnaire was administered to graduate students (n = 25), followed by an end of semester questionnaire in a mandatory public health course. Differences (orienta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…In considering search behaviour, Bourgeois (2022) undertook a questionnaire survey of first‐year public health students to compare reported and actual engagement with library resources and services. They found that graduate students had realistic expectations of the library resource use, and that their confidence in their ability to use library resources grew as the teaching programme continued.…”
Section: In This Issue…mentioning
confidence: 99%
“…In considering search behaviour, Bourgeois (2022) undertook a questionnaire survey of first‐year public health students to compare reported and actual engagement with library resources and services. They found that graduate students had realistic expectations of the library resource use, and that their confidence in their ability to use library resources grew as the teaching programme continued.…”
Section: In This Issue…mentioning
confidence: 99%